The Relationship Between Perceived Leader Busyness and Perspective Taking and Interaction Behavior of Followers - Huang, Qiufeng; Zhang, Kaili (Frontiers in Psychology, 2021)
How leaders influence followers has been a hot topic in both research and practice. Yet, prior studies have primarily focused on the impact of one leadership style, while overlooking how a leadership role may influence leaders’ behavioral expressions. Particularly, being a leader means having to face time demands and workload pressure and thus busyness becomes a common phenomenon for leaders. Focused on perceived leader busyness, we examined how it may influence employee interactions with leaders and how those interactions influence leader evaluations of followers’ performance. Based on sensemaking theory, we propose that when followers have a high-level of perspective taking, they are more likely to take avoidance behavior when perceive leaders as of high busyness. Further, when followers engage in interaction avoidance behavior, leaders may consider followers as hiding errors or intentionally concealing their work process, which reduces positive evaluations (i.e., task performance and conscientiousness evaluation) while enhancing negative evaluation (i.e., deviance behavior) toward followers. We conducted two studies. Study one was conducted with a 25-participants interview and 297 employees’ data to show scale validity of perceived leader busyness. Study two was conducted with 377 employees and their direct supervisors. Applying the complex modeling method, we found that followers with low-level perspective taking are less likely to engage in interaction avoidance behavior, even when perceiving leaders as high busyness; followers’ interaction avoidance behavior has a positive relationship with leaders’ counterproductive behavior evaluation, but a negative relationship with conscientiousness behavior evaluation. This study enriches the dyadic interactions between leaders and followers. In addition, it also shows the burden of perspective taking.